2018
DOI: 10.1002/ptr.6127
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of cinnamon bark extract against ischemia–reperfusion injury and arrhythmias in rat

Abstract: Cinnamomum zeylanicum (cinnamon) is a plant with potent antioxidant activity and has been used in traditional medicine for improvement of heart function. The effects of cinnamon bark ethanolic extract were investigated against ischemia-induced arrhythmias and heart injury in an in vivo rat model of regional heart ischemia. The extract was also standardized, and its antioxidant activity was evaluated. Adult male Sprague-Dawley rats were subjected to 30 min of ischemia by occlusion of the left anterior descendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Thus, it is a common occurrence following cerebral infarction, stroke, myocardial infarction, organ transplantation, and trauma . Clinical treatment of IRI includes therapeutic hypothermia, hydrogen sulfide treatment, cyclosporine, cannabinoids, superoxide dismutase, metformin, and stem cell therapy . IRI is still a life‐threatening risk to the patients because it causes inflammatory cytokine storm, arrhythmias, and infarction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is a common occurrence following cerebral infarction, stroke, myocardial infarction, organ transplantation, and trauma . Clinical treatment of IRI includes therapeutic hypothermia, hydrogen sulfide treatment, cyclosporine, cannabinoids, superoxide dismutase, metformin, and stem cell therapy . IRI is still a life‐threatening risk to the patients because it causes inflammatory cytokine storm, arrhythmias, and infarction.…”
mentioning
confidence: 99%
“…3 Clinical treatment of IRI includes therapeutic hypothermia, hydrogen sulfide treatment, cyclosporine, cannabinoids, superoxide dismutase, metformin, and stem cell therapy. 4 IRI is still a life-threatening risk to the patients because it causes inflammatory cytokine storm, arrhythmias, and infarction. However, the exact pathophysiological and biological mechanisms of IRI remain incompletely understood.…”
mentioning
confidence: 99%
“…This is related to the ability of polyphenols to prevent LDL cholesterol oxidation. For example, Olea europaea, Cinamomum Spp and Artemisia dracunculus cause a decrease in cholesterol levels and lipid peroxidation as well as an increase in antioxidant enzymes [56,69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, cinnamon has been long used as a traditional medicine in the treatment of many conditions, such as bronchitis, rheumatism, and neuralgia . Furthermore, many modern scientific articles report on the ability of cinnamon to be antidiabetic, antioxidant, anti‐inflammatory, anti‐fungal, anti‐HIV, improve heart function, pro‐wound healing, and anti‐cancer . It has been reported that cinnamaldehyde holds remarkable anti‐microbial activity …”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, many modern scientific articles report on the ability of cinnamon to be antidiabetic, antioxidant, anti-inflammatory, antifungal, anti-HIV, improve heart function, pro-wound healing, and anti-cancer. [5][6][7][8][9][10] It has been reported that cinnamaldehyde holds remarkable anti-microbial activity. [11][12][13][14] Candida albicans is found in abundance in the human gut flora of around 50% of all healthy adults and is an opportunistic pathogenic yeast.…”
Section: Introductionmentioning
confidence: 99%